Estudo químico e reológico de ligantes asfálticos modificados por polímeros e aditivos. - Bringel, Raquel Moraes (2007)
The Brazilian asphalt binder from Fazenda Alegre oil reserve (CAPFA) in the state of Espírito Santo, was modified by polymers (SBS and EVA) additives (oil extensor, hydrated lime and LCC). The main structural characteristics of this pure and modified binder were analyzed using the spectroscopic methods (RMN and FTIR), thermal analysis (TGA, DSC) and through microscopy (AFM). The polymers and additives were characterized through thermogravimetry (TG), differential scanning calorimetry and infrared spectroscopy. The asphaltic binder modified by polymers and additives, and the resulting rheological effects of this modification, were also evaluated. The methodology that was applied was oriented mainly towards the evaluation of the constitutive properties of the materials, using rheological tests based on the Superpave specifications. The parameters investigated aimed the evaluation of the usual distresses such as: permanent deformation, thermal cracking and oxidation. The oxidative ageing of the asphalt was evaluated from analysis in the infrared and nuclear magnetic resonance, as well as the variations of the rheological parameters. The thermal stability of the CAPFA (pure and modified) and of the asphaltenic was analysed through the TG curves. This stability looks as if it is influenced by the secondary reactions of decomposition and/or oxidation of the products and residuals that have been formed. The two main constituent fractions of the asphaltic binder were separated: the asphaltenic (17,1%) and maltenic (82,9%). The calculation of the molar mass of the asphaltenic by osmometry and GPC demonstrated very similar values (5963 and 6653 g/mol). Images of the binders obtained through the use of atomic force microscopy (AFM) show the coexistence of a rich phase in asphaltenic in equilibrium. Images (AFM) of the binder while modified by a polymer suggest that part of the maltenic fraction is absorbed by the polymer. The most significant effect of the polymer incorporation to the asphalt was the improvement of the elasticity. There is a strong correlation between the deformation resistance at high temperature and G*. For the modified asphalt binder, a significant increase was noted in G* in lower frequencies, where a network of the polymers SBS and EVA are particularly dominant, and a small decrease on G* in higher frequencies. It was also observed a decrease in the tan δ and this indicates that the formation of a 10 polymeric network, which gives the binder an elastic stability at higher temperatures, has occurred. The addition of SBS and EVA to the CAPFA lead to an increase of the hardness and the elasticity of the asphalt binder, but among the asphaltic mixtures produced, it was observed, before and after ageing, that the binder modified by the EVA and the hydrated lime demonstrated a higher stiffness and the binder modified by the SBS demonstrated a higher elasticity. The susceptibility relative to the temperature of the asphalt mixtures measured through the flow activated energy, demonstrated that the mixtures containing EVA degrade themselves less than those that contain SBS. This happens due to the fact that there is no butadiene double bond in the polymer EVA that easily oxidizes, like in the case of the SBS. The additives present in the mixtures with the EVA polymer also contributed to a lower sensitivity to the temperature, once the hydrated lime reduces the ageing of the asphalt mixture through the interaction with the reactive polar molecules present in the asphalt binder and CNSL it is an excellent antioxidant. In regards to the stability of the storage of the modified asphalt by SBS, apparently occurs a “break” of the colloidal polymer-asphalt structure in higher frequencies.